O mecanismo de desenvolvimento limpo (MDL) e transferência de tecnologia: o projeto de MDL do aterro sanitário de Salvador - Nápravník Filho, Luciano Angelo Francisco Karel (2009)
This study aims to verify technology transfer occurrence in the Clean Development Mechanism (CDM). This study object serves as an economic motivation for nations that need to reduce their carbon dioxide emission rates during the 2008-2012 marking period. The CDM takes all practicable steps to promote, facilitate and finance, the transfer of, or access to, environmentally sound technologies, know-how, practices and processes pertinent to climate change, in particular to developing countries. Initially, it was necessary to understand the meanings of technology and technology transfer; as well as, clean technology and clean technology transfer. Consecutively, it was necessary to comprehend the Clean Development Mechanism as a clean technology transfer tool. In both cases, it were used documental and bibliographic researches as the cornerstones for constructing the theoretical review and the model analysis. By means of an exploratory single Case Study, it was analyzed a clean technology transfer process in the Clean Development Mechanism, specifically saying, Salvador s Landfill Gas CDM Project, entitled: Projeto do Aterro Sanitário de Salvador . Thus, it was verified that, Salvador s Landfill Gas CDM Project, in fact, plays an important role in mitigating the effects of the global warming, but in what concerns the technology transfer, it lacks significantly in terms of project execution. The technological transfer that occurs in a typical CDM project resembles a lot to those of other organizational projects that do not draw heavily on the CDM s philosophy. The project s case study permits saying that the technology transferred in it can not be considered as a clean one.